Teknik Pengendalian Hama Tikus dengan Metode Gropyokan Di Desa Sumbersari Kecamatan Sumberharta - Sumini, Sumini; Wartono, Wartono; Alfiana, Alfiana (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Rice plants are the main food source in Indonesia which has the potential to continue to be increased in supporting rice self-sufficiency with significant production. However, rat pest attacks can reduce rice production by up to 37%. Through this community service program, the aimed is for farmers in Sumbersari Village, Sumberharta District to be able to carry out more efficient and effective pest control techniques through the gropyokan method. This activity will take place from June to August 2024 and will involve the active participation of more than 80% of local farmers. The results of this gropyokan activity showed that more than 500 rats were successfully caught. This activity also showed that rat pest attacks decreased by 30% after the implementation of the activity. Besides that, this program not only increases the effectiveness of pest control but also strengthens solidarity and cooperation between farmers. Awareness of the importance of environmentally friendly methods in pest control is growing, encouraging farmers to schedule regular gropyokan activities. This activity not only provides a practical solution to the problem of rat pests, but also fosters a spirit of collaboration and environmental awareness among village communities.